A Breath of Fresh Air - Chunawala, Aafreen; Jain, Pratik (Homœopathic Links, 2018)
Asthma affects individuals of all ages, from childhood into adulthood. Taking preventive measures is essential for asthmatic patients, as the recurrence of attacks is a major discomfort and stressor. Here, we will examine two cases of bronchial asthma from the practices of conscientious students who have learned under Dr. Rajan Sankaran. Here, the authors demonstrate the ease in which neo-homeopaths can also emulate Dr. Sankaran's various approaches and techniques of case taking and analysis, and also how to apply these very techniques to find a carefully selected medicine that brings a successful cure. Homeopathic remedies become ‘a breath of fresh air’ for these patients and provide long-term relief of symptoms, both physically and mentally.
Keywords: Calcarea Sulphurica; Nux vomica; Synergy; Bronchial asthma; PNEI axis; Loganiaceae; Typhoid; Sensation; Miasm; Genius